Study of income and food consumption expenditure households of wet-rice farmers in West Sumatra, Indonesia - Sentosa, Sri Ulfa; Satrianto, Alpon; Akbar, Urmatul Uska; Ariusni; Yeni, Intan Putri (Asian Journal of Agriculture and Rural Development, 2025)
This study aims to analyze socio-economic factors affecting the per capita income of households of wet-rice farmers, socio-economic factors affecting food consumption expenditure of these households, and to calculate income elasticity. The study employs a quantitative design, utilizing a multistage sampling method to determine the sample. The total sample size consisted of 349 farmer households. Data were analyzed using Two-Stage Least Squares regression. Based on the analysis, the following findings were obtained: 1) Variables such as food consumption expenditure, technical efficiency, off-farm work, diversification in agriculture, land tenure status, access to credit, and education have a positive and significant influence on the per capita income of farm households. 2) Variables including per capita income, access to credit, age, location, marital status, and education have a positive and significant influence on the per capita food consumption expenditure of farmer households. 3) Income elasticity for all quantiles has a value of E<1, indicating the applicability of Engel’s law. This study provides comprehensive insights into the economic behavior of paddy field farming households by examining both the determinants of household income and food consumption expenditure. It also discusses policy implications for food availability, food consumption quality, food diversity, and poverty alleviation policies.